Reconstructing Moral Internalization in Islamic Religious Education for Generation Z in the Digital Era - Mohammad Hafid Ardiasyah; Muhammad Ubaydillah; Ansori (Civiliza Publishing, Indonesia., 2026)
The rapid advancement of digital technology has significantly transformed the processes of learning, communication, and moral development among Generation Z, creating new challenges for Islamic Religious Education (IRE). Conventional approaches to moral internalization, which primarily emphasize knowledge transmission, role modeling, and habituation, require conceptual reconstruction to remain relevant in digitally mediated educational environments. This study aims to reconstruct the concept of moral internalization in Islamic Religious Education for Generation Z in the digital era through an integrative literature review. The study systematically synthesized scholarly publications on Islamic education, moral education, character development, digital pedagogy, and Generation Z to develop a comprehensive conceptual framework. The findings indicate that effective moral internalization should no longer be understood as a linear pedagogical process but as a multidimensional and transformative educational process integrating cognitive understanding, spiritual awareness, emotional engagement, digital ethical literacy, social participation, and reflective practice. The proposed framework also emphasizes the collaborative roles of teachers, families, educational institutions, and digital environments in fostering sustainable moral development. Theoretically, this study contributes by expanding existing perspectives on Islamic Religious Education through a contextually responsive conceptual model suitable for contemporary digital societies. Practically, the reconstructed framework provides valuable guidance for curriculum development, instructional innovation, teacher professional development, and educational policy aimed at strengthening moral education for Generation Z while preserving the fundamental ethical principles of Islamic education amid ongoing digital transformation.